2015
DOI: 10.1371/journal.pone.0136693
|View full text |Cite
|
Sign up to set email alerts
|

Association of Nitric Oxide Synthase and Matrix Metalloprotease Single Nucleotide Polymorphisms with Preeclampsia and Its Complications

Abstract: BackgroundPreeclampsia is one of the leading causes of maternal and neonatal morbidity and mortality in the world, but its appearance is still unpredictable and its pathophysiology has not been entirely elucidated. Genetic studies have associated single nucleotide polymorphisms in genes encoding nitric oxide synthase and matrix metalloproteases with preeclampsia, but the results are largely inconclusive across different populations.ObjectivesTo investigate the association of single nucleotide polymorphisms (SN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 53 publications
2
18
1
1
Order By: Relevance
“…Also, the eNOS 894T allele is subject to selective proteolytic cleavage in ECs and vascular tissues, and this could account for the reduced vascular NO generation in homozygous subjects for this variant (Alpoim et al, 2014). The T−786C allele is also increased in PE compared with Norm-Preg women (Ben Ali Gannoun et al, 2015; Leonardo et al, 2015). Paternal genes may also play a role, and a paternal history of PE was associated with a 2.7% risk of PE when compared to men whose mothers had normal pregnancy (Esplin et al, 2001).…”
Section: Risk Factors For Endothelial Dysfunction In Preeclampsiamentioning
confidence: 96%
“…Also, the eNOS 894T allele is subject to selective proteolytic cleavage in ECs and vascular tissues, and this could account for the reduced vascular NO generation in homozygous subjects for this variant (Alpoim et al, 2014). The T−786C allele is also increased in PE compared with Norm-Preg women (Ben Ali Gannoun et al, 2015; Leonardo et al, 2015). Paternal genes may also play a role, and a paternal history of PE was associated with a 2.7% risk of PE when compared to men whose mothers had normal pregnancy (Esplin et al, 2001).…”
Section: Risk Factors For Endothelial Dysfunction In Preeclampsiamentioning
confidence: 96%
“…268 The T786C allele is also increased in preeclamptic compared with normal pregnant women. 269,270 Genetic polymorphisms of eNOS could affect NO production. For instance, normal pregnant women with the TT phenotype for the T-786C allele have lower plasma nitrite levels than those with the CC phenotype 271 , and the TT phenotype has been proposed as a risk factor for preeclampsia in Tunisian women.…”
Section: Mmps and Vascular Dysfunction In Hypertensive Pregnancy Amentioning
confidence: 99%
“…Many previous investigations have shown that several environmental factors play a key role in the pathogenesis of preeclampsia, such as preexisting hypertension, family history of the disease, lack of vitamin C, and vascular endothelial injury (Dekker et al, 2011). Previous studies have shown that polymorphisms in many genes are associated with preeclampsia risk, notably in those encoding nitric oxide synthase 3, dopamine receptor D1, DRD4, lymphotoxin-a, matrix metalloprotease, transforming growth factor-b1 (TGF-b1), cyclooxygenase 2, and plateletactivating factor acetylhydrolase (Deepthi et al, 2015;Leonardo et al, 2015;Pissetti et al, 2015;Ren et al, 2015;Su et al, 2015;Wolski et al, 2015;Zeng et al, 2016).…”
Section: Introductionmentioning
confidence: 99%